In vivo antiplasmodial activities of Nauclea latifolia - Ette, Ettebong Okon; Ubulom, Edwin P.M.; Ekpenyong, Edet C.; Ekong, Samuel U.; Akpan, Ezekiel O.; Tambari, Domu V. (Asian Journal of Medical Sciences, 2014)
Background: The plant Nauclea latifolia is widely used in the southern parts of Nigeria for the treatment of malaria. Malaria is the number one killer disease in Nigeria. WHO reports that malaria continues to cause approximately 207 million cases of infection around the world and kills yearly about 627,000 people. It still kills a child somewhere in the world every minute. The study was aimed at evaluating the in vivo antiplasmodial activities of the extract and fractions (n-hexane, chloroform, ethyl acetate, butanol, aqueous) of the stembark in Plasmodium berghei berghei infected mice. Methods: Through oral administration of the extract (100, 200 and 300mg/kg) and fractions (200mg/kg), antiplasmodial activities were screened using 4-day suppressive, 7-day curative and repository tests. Significance was determined using ANOVA followed by Tukey-Kramer multiple comparison post- test using Graphpad Instat 3.10. A probability level of less than 5% was considered significant. Results: The extract exhibited significant dose-dependent antiplasmodial activity in the suppressive and repository tests. A significant (p<0.05-0.001) dose-dependent reduction in parasitaemia in extract-treated groups in curative test was also observed. The aqueous fraction had the highest percentage chemosuppressive effect (67.71%).The extract also dose-dependently increased the survival days of the infected mice. The preliminary phytochemical investigation showed the presence of alkaloids, saponins, tannins, flavonoids and cardiac glycosides. Conclusion: This result confirmed the ethnobotanical use of the plant as malarial remedy and calls for further investigation of its phytochemical components and its antimalarial potentials. DOI: http://dx.doi.org/10.3126/ajms.v6i3.11361 Asian Journal of Medical Sciences Vol.6(3) 2015 6-11